2006
DOI: 10.1088/0957-4484/17/5/059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on the ferromagnetism of Mn-doped ZnO nanoparticles and Mn-related Raman vibration

Abstract: Mn-doped ZnO nanoparticles were synthesized by a rheological phase-reaction–precursor method and the thermal decomposition of the oxalate precursors was studied by thermogravimetry and differential thermal analysis in air. The Mn-doped ZnO obtained at lower temperature crystallizes in a wurtzite structure and a new phase appears at higher temperature. The lattice parameters of Zn1−xMnxO (0.09≤x≤0.1) increase gradually with increasing temperature up to 650 °C and then decrease. X-ray photoelectron spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 31 publications
7
53
0
Order By: Relevance
“…[20] In contrast, Cong et al argued that the peak at 524-527 cm −1 is due to the vibration of the Mn atom at the Zn site. [24] Another marked assignment for the peak P 2 has been proposed recently by Zhong et al, who calculated the local phonon density of states (LPDOS) of the Mn and Zn atoms in Mn + -implanted ZnO using the real-space recursion method. [25] The results showed that the peak at 527 cm −1 will only appear in the Zn atom's LPDOS where Mn atoms partially replace O atoms in the ZnO crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
“…[20] In contrast, Cong et al argued that the peak at 524-527 cm −1 is due to the vibration of the Mn atom at the Zn site. [24] Another marked assignment for the peak P 2 has been proposed recently by Zhong et al, who calculated the local phonon density of states (LPDOS) of the Mn and Zn atoms in Mn + -implanted ZnO using the real-space recursion method. [25] The results showed that the peak at 527 cm −1 will only appear in the Zn atom's LPDOS where Mn atoms partially replace O atoms in the ZnO crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc oxide is one of such materials that have received special interest because it has both charge and spin degrees of freedom in a single matrix, which lead to the interplay of functionalities (magnetic and electronic). Also the oxalates from the 3d metals such as zinc are isomorphous in nature, which enables the enhancement of physical properties of oxide semiconductors by doping the precursor in the course of synthesis [2][3][4][5][6]. Many research groups that have worked on doping with transition metals have used zinc oxide as a good host material for realizing wide band-gap dilute magnetic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many Mn-doped ZnO systems have been synthesized by different methods (ion implanta-tion, RF magnetron sputtering, solid state reaction, pulsed laser deposition, molecular beam epitaxy, sol-gel process, hydrothermal or solvothermal) and extensively studied but controversial results are reported [6][7][8][9][10][11][12][13][14]. The magnetic properties of Mn-doped ZnO have been widely studied and different magnetic behaviors, like spin-glass, paramagnetic, antiferromagnetic and ferromagnetic, have been found [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%